1995
DOI: 10.1172/jci118198
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences of polymorphism of an immunoglobulin VH3 gene.

Abstract: The VH26 germline gene occupies two different loci, due to gene duplication, and is one of the most frequently expressed human immunoglobulin VH genes. This report identifies the alleles of each VH26 locus and describes distinct patterns of VH26 polymorphism in three ethnic groups. Oligonucleotide probes targeting VH26 were used in sequence-specific RFLP analysis of DNA from 72 Caucasians, 52 Asians, 35 American Blacks, and members of six families. The A locus, on a 7.0-kb TaqI band, was detected in 89% of Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 49 publications
(50 reference statements)
3
33
0
Order By: Relevance
“…It has been shown that the rate of nonsynonymous nucleotide substitution is significantly higher than that of synonymous substitution at the complementarity-determining regions of V H and V L genes (47). This observation once suggested the possibility that V H and V L genes might also be subject to overdominant selection, but recent studies have shown that the extent of V H or V L gene polymorphism within loci is much lower than that of MHC genes (48)(49)(50). Therefore, it seems that a higher rate of nonsynonymous substitution than that of synonymous substitution in V H and V L genes is caused by directional selection rather than overdominant or balancing selection.…”
Section: Evolution Of Immunoglobulin Genesmentioning
confidence: 99%
“…It has been shown that the rate of nonsynonymous nucleotide substitution is significantly higher than that of synonymous substitution at the complementarity-determining regions of V H and V L genes (47). This observation once suggested the possibility that V H and V L genes might also be subject to overdominant selection, but recent studies have shown that the extent of V H or V L gene polymorphism within loci is much lower than that of MHC genes (48)(49)(50). Therefore, it seems that a higher rate of nonsynonymous substitution than that of synonymous substitution in V H and V L genes is caused by directional selection rather than overdominant or balancing selection.…”
Section: Evolution Of Immunoglobulin Genesmentioning
confidence: 99%
“…Previous reports suggested that polymorphic gene duplication may frequently occur in Ig loci including 14q32.33 (Ig heavy variable cluster) and 22q11.2 (Ig heavy chain constant region and Ig lamda) (Sasso et al, 1995;van der Burg et al, 2002;Buckland et al, 2003). It is likely that the copy number variation of the Ig loci may not be from the germ line but a de novo CNV enriched during LCL generation.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] The V H and V L gene sequences consistently revealed significant deviations from the germline V H and V L genes. Although some of the detected nucleotide changes may be due to genetic polymorphisms, [41][42][43] most of them likely represented somatic mutations. Analyses of the mutation patterns indicated not only stimulation, but also selection by antigen, based on the accumulation of R mutations on CDR in most of the cases (see Table 2).…”
Section: Discussionmentioning
confidence: 99%